2020
DOI: 10.4103/aam.aam_63_19
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of patients with adrenal insufficiency

Abstract: Background: Adrenal insufficiency (AI) is a rare and a dangerous disease requiring a life-long glucocorticoid replacement therapy with dose adjustment in stressful situations which is linked to patient's knowledge and understanding. The aim of this study was to explore AI patients understanding regarding their disease, risk factors of adrenal crisis, as well as their attitude in stressful situations. Materials and Methods: We prospectively enrolled from October to Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Our Africa-wide survey [ 9 ] revealed the use of a wide variety of glucocorticoid replacement therapies, including hydrocortisone, prednisone, methylprednisolone, and dexamethasone, depending on availability with a greater range available in the private health system, compared to the public health system (44.0% vs. 17.2%; p < 0.001). In a survey examining the knowledge and attitude of patients with adrenal insufficiency, Bouziane et al [ 82 ] found that 74% of the patients did not have sufficient understanding of their disease and the risks associated with it, including crises precipitated by stress and sickness requiring dose adjustments. In Tunisia, Chihaoui et al [ 83 ] reported that adult Muslim populations in predominantly North African regions who uphold Ramadan have the attendant risk of potentially lethal hypoglycaemic events.…”
Section: Resultsmentioning
confidence: 99%
“…Our Africa-wide survey [ 9 ] revealed the use of a wide variety of glucocorticoid replacement therapies, including hydrocortisone, prednisone, methylprednisolone, and dexamethasone, depending on availability with a greater range available in the private health system, compared to the public health system (44.0% vs. 17.2%; p < 0.001). In a survey examining the knowledge and attitude of patients with adrenal insufficiency, Bouziane et al [ 82 ] found that 74% of the patients did not have sufficient understanding of their disease and the risks associated with it, including crises precipitated by stress and sickness requiring dose adjustments. In Tunisia, Chihaoui et al [ 83 ] reported that adult Muslim populations in predominantly North African regions who uphold Ramadan have the attendant risk of potentially lethal hypoglycaemic events.…”
Section: Resultsmentioning
confidence: 99%
“…[1] The role of the patient in recognizing when an increase in glucocorticoid doses is required is central to minimize the risk to themselves; thus, the importance of patient education is repeatedly emphasized. [2,3] Published existing literature has identified deficiencies in the patients' understanding of steroid sick day rules, [2,4] how to administer parenteral hydrocortisone, [2,4,5] and when to seek medical attention. [2] However, reports highlight gaps in clinician knowledge, particularly on the recognition, and the management of AI.…”
Section: Commentarymentioning
confidence: 99%
“…[2,3] Published existing literature has identified deficiencies in the patients' understanding of steroid sick day rules, [2,4] how to administer parenteral hydrocortisone, [2,4,5] and when to seek medical attention. [2] However, reports highlight gaps in clinician knowledge, particularly on the recognition, and the management of AI. [4,[6][7][8] Given that healthcare professionals have a central role in patient education, it is essential that clinicians, irrespective of grade are familiar with steroid sick day rules and pharmacokinetics to avoid preventable adverse patient outcomes.…”
Section: Commentarymentioning
confidence: 99%